Basic approaches to personnel health management in the workplace - J. N. Skulkina (Здоровье мегаполиса, 2022)
Introduction. Corporate health and well-being programsare becoming more relevant as they allow organizations not only to manage risk factors in the field of personnel health, but also to reduce the costs associated with the loss of ability of employees, and also contribute to the growth of labor productivity and team engagement In fact, more and more evidence indicates that workplace interventions based on a coordinated, planned and integrated approach to improving the health of workers are more effective than traditional individual measures for a healthy lifestyle. Target. The purpose of this article is to describe the main approaches to the development of “healthy jobs”, the features of the implementation of corporate health promotion programs.Materials and methods. The research is based on the analysis of scientific literature, regulatory legal acts. Open data was used as a source of information. Results. The article discusses the concept and main components of health promotion programs in the workplace, foreign approaches, government programs and initiatives of world campaigns for the development of “healthy workplaces”, and features of the implementation of corporate health management programs.